Indicadores termográficos, clínicos e laboratoriais para o diagnóstico precoce da mastite em fêmeas bovinas - Gertrud Elisa Campos Edler (2013)
This study aimed to evaluate clinical, laboratory and thermography for early ability mastitis’s detection in dairy cows of different parity. Analyzes were performed clinical and laboratory findings of 123 cows. The experiment were conducted in first sixty moth of lactation . The clinical examination and udder examination was performed 24 hours before milking and thermography, strip cup, CMT (California Mastitis Test), SCC (Somatic Cell Count), BC (Bacterial Count) was performed instantly before milking. Thermography was conducted at two moments pre-milking and post-milking and in different projections. The thermography ability in early detection of subclinical mastitis was determined. There was sensitivity 80 % and specificity 25,9 % in 200 x 103 CCS cut off and 30 x 103 BC cut off the sensibility was 80 % and specificity 42,57 %. The better projections for mammary thermography was caudal projection for rear quarters and side projection for front quarters. The mammary thermography can be conducted pre-milking and post-milking without prejudice to detection of subclinical mastitis.